Manual on Religious and Spiritual Accommodation - (:unkn) unknown (My University, 2016)
This resource book gathers together information regarding the accommodation of thereligious and spiritual needs of the people serving federal sentences, drawing on theexperience and wisdom of both faith communities of Canada and the CorrectionalService of the Canadian population. It reflects the increasing cultural and religiousdiversity of Canada and the desire on the part of CSC to respect the rights of offenders topractise their faith during their incarceration.